Design and fabrication of tiger nut juice extractor - N.A. Raji; K.A. Adedeji; J.O. Olaleye; F.A. Adele (Journal of Applied Sciences and Environmental Management, 2019)
Tiger nut tuber is rich in energy content, nutrients and minerals. The tuber which is usually stored dried could be processed by rehydration to improve the extraction of the milk content. The machine is developed to extract the milk contents of the crop for purpose of consumption and other usages. The design is made of the feeding segment, the extraction segment, power segment and the frame support which serves as the machine subassemblies. The design of the screw and drive mechanism is emphasize to ensure efficient performance of the machine. The machine is driven by a belt drive system powered by a 2 hp. electric motor operating at a speed of 1100 rpm. The efficiency of the machine is within the range of 53-55% for a power requirement of 1.514 kW. The machine is found suitable for small scale operation.